2019
DOI: 10.21608/ajfm.2019.43103
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Acute Antipsychotic Poisoned Cases Admitted to Tanta University Poison Control Unit

Abstract: Background: Sedative hypnotic/antipsychotic poisoning represented 5.84% of cases according to national poison data system in 2017. In Egypt, studies about antipsychotic poisoning are scarce. Objectives: is to assess the pattern of toxicity and prognosis of cases with acute antipsychotic poisoning admitted to Tanta University Poison Control Unit. Patients and Methods: This study was conducted on cases who admitted to Tanta University Poison Control Unit with acute antipsychotics poisoning. All cases were subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
(46 reference statements)
2
7
0
Order By: Relevance
“…Compared to the accidental group in the current study, the suicidal poisoning group had a significant association with a history of psychiatric illness (19.4% versus 5.3%, p = 0.033) and therapeutic psychiatric drug administration (16.2% versus 2.6%, p = 0.027). These findings are harmonious with the results of previous researchers [ 34 , 35 ] who revealed that 13% and 31.6% of suicidal poisoned patients, respectively, had pre-existing psychiatric disorders. Nistor and colleagues [ 36 ] also concluded that psychological disturbance increases the risk of suicidal poisoning by 11% to 27% more than the overall population.…”
Section: Discussionsupporting
confidence: 91%
“…Compared to the accidental group in the current study, the suicidal poisoning group had a significant association with a history of psychiatric illness (19.4% versus 5.3%, p = 0.033) and therapeutic psychiatric drug administration (16.2% versus 2.6%, p = 0.027). These findings are harmonious with the results of previous researchers [ 34 , 35 ] who revealed that 13% and 31.6% of suicidal poisoned patients, respectively, had pre-existing psychiatric disorders. Nistor and colleagues [ 36 ] also concluded that psychological disturbance increases the risk of suicidal poisoning by 11% to 27% more than the overall population.…”
Section: Discussionsupporting
confidence: 91%
“…Despite it was a non-significant association, it is a clinically important finding that might be more pronounced in future research including a larger sample size. Supporting evidence has been reported by Mubarak et al 4 who found a significant association between GCS and the duration of hospital stay. Moreover, they demonstrated a low GCS as a predictor of the prolonged hospital stay.…”
Section: Discussionsupporting
confidence: 81%
“…6,28,33,34 Moreover, a high frequency of prolonged QTc interval in atypical antipsychotics poisoning has been observed in a recent prospective analysis of patients admitted with acute antipsychotics poisoning. 4 Prolongation of QTc interval is a life-threatening complication of various atypical antipsychotics overdose. It may induce lethal arrhythmia including torsade de pointes and ventricular fibrillation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rug ingestion is the commonest cause of acute poisoning among children according to poison control centers records all over the world. A great percent of hospital admission cases involves drug poisoning, particularly with psychotropic drugs such as sedatives, antidepressants, and neuroleptics (Watson et al, 2004;Gummin et al, 2017;Mubarak et al, 2019).…”
Section: Introductionmentioning
confidence: 99%